2012
DOI: 10.3102/0002831211431006
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Teaching Practice and Early Career Decisions

Abstract: Although the turnover rate among beginning teachers has been a major concern for some time, most studies do not link teacher retention with teaching practice. In contrast, this study looks specifically at career decisions coupled with practice. Guided by a view of teaching as social and cultural practice, the study used multiple qualitative data sources, including extensive observations, interviews, and samples of teachers' and students' work. Based on within and cross-case analysis of 15 cases at four distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 31 publications
0
42
0
11
Order By: Relevance
“…The highest turnover is attested among beginner teachers in their first years of service and among the pre-retirement age group [Grissmer, Kirby 1997;Liu, Ramsey 2008]. The high turnover among beginner teachers is explained mostly in terms of (un)successful adaptation to the profession, often with reference to professional identity formation [Cochran-Smith et al 2012]. The high turnover in the pre-retirement group is best explained by the high pension-to-salary ratio for US teachers, which makes early retirement attractive [Harris, Adams 2007].…”
Section: Empirical Data On Teacher Turnovermentioning
confidence: 99%
“…The highest turnover is attested among beginner teachers in their first years of service and among the pre-retirement age group [Grissmer, Kirby 1997;Liu, Ramsey 2008]. The high turnover among beginner teachers is explained mostly in terms of (un)successful adaptation to the profession, often with reference to professional identity formation [Cochran-Smith et al 2012]. The high turnover in the pre-retirement group is best explained by the high pension-to-salary ratio for US teachers, which makes early retirement attractive [Harris, Adams 2007].…”
Section: Empirical Data On Teacher Turnovermentioning
confidence: 99%
“…Smith and Ingersoll also found that the largest reduction in turnover was associated with induction support that engaged novices into collaborative networks with more experienced peers. There is no doubt that isolation and a lack of access to professional development have an adverse affect on the retention of novice special educators (Kozleski et al, 2000), even those who are among the most competent graduates (Cochran-Smith et al, 2012;Jones, 2009;Smith & Ingersoll, 2004). On the other hand, novice special educators have a much higher probability of becoming tomorrow's veteran teachers if given access to a comprehensive, welldesigned induction support program that engages them in collaborative networks with more experienced peers (Billingsley, 2004;Carr & Evans, 2006;Little & King, 2008).…”
Section: Induction Support For Novice Special Educatorsmentioning
confidence: 99%
“…Some teacher education programs develop professional development schools to meet students' field experience needs (Klingner et al, 2004), but this approach does not offer the variety of experiences needed to be adequately prepared for service (Epanchin & Colucci, 2002;Jenkins et al, 2002). Others programs provide an office of field experiences that assigns students to schools and employs clinical instructors to supervise fieldwork (Cochran-Smith et al, 2012). This model, however, can result in a lack of quality control because there is no assurance that the practices observed in the field will match the pedagogy taught during personnel preparation (Epanchin & Colucci, 2002;Prater & Sileo, 2002, 2004.…”
Section: The Challenges To Community Building Field Experience and Prmentioning
confidence: 99%
“…There has been considerable research into ECTs' practices and how preservice teacher education program can best meet the needs of soon-to-be ECTs (Cochran-Smith et al, 2012;Darling-Hammond, 2006, 2012Flores & Day, 2006). Many have noted that time is a factor in teachers' professional development as teaching is a multifaceted undertaking.…”
Section: Ects' Development Of Teaching Practicesmentioning
confidence: 99%
“…There is considerable interest in understanding more about how pre-service teachers (PSTs) grow and change as they move from teacher education programs into their first years of teaching (Beck & Kosnick, 2014;Cochran-Smith et al, 2012;Caudle & Moran, 2012;Grossman et al, 2000;Jones & Enriquez, 2009). We conducted a longitudinal study from 2012 to 2016 examining the transfer of learning about literacy practices from a preservice teacher education program to the secondary classrooms of early career teachers (ECTs).…”
Section: éTude De Cas Exploratoire Sur Une Pratique Professionnelle Ementioning
confidence: 99%